Abundance estimates for sperm whales in the Mediterranean Sea from acoustic line-transect surveys - Lewis, Tim; Boisseau, Oliver; Danbolt, Magnus; Lacey, Claire; Leaper, Russell; Matthews, Justin; McLanaghan, Richard; Moscrop, Anna (J. Cetacean Res. Manage., 2023)
The Mediterranean sub-population of sperm whales is believed to be isolated and is classified as Endangered on the IUCN Red List. Although there is evidence to suggest the population is declining, there is a lack of abundance data. A series of acoustic line-transect surveys were undertaken between 2004 and 2013. In 2004, 3,946km of acoustic effort was conducted in the southern Western Mediterranean basin, resulting in the detection of 159 sperm whales. While in 2007 and 2013, 10,276km of acoustic effort was conducted in the Eastern Mediterranean basin, resulting in the detection of 24 sperm whales. A pooled detection function gave an effective strip half-width of 9.8km. A correction for availability bias was made for each block based on published simulations using data on sperm whale acoustic behaviour: estimates of g(0) were 0.95–0.96. Estimated abundances were: Southern Western Mediterranean Block 634 animals [374–1,077] (95% log-normal confidence interval); Hellenic Trench Block 41 [17–100]; Central Aegean Sea Block 33 [5–203]; Herodotus Rise Block 5 [1–28] and Southern Adriatic Sea Block 2 [0–12]. Estimates for all other blocks were zero. The density of sperm whales in the surveyed Southern Western Mediterranean Block was over 17 times higher than for the surveyed Eastern Mediterranean (2.12 and 0.12 whales per 1,000km² respectively). These results, combined with an acoustic survey of the northern Ionian Sea in 2003 and aerial surveys in the northern Western Mediterranean basin in 2010–11, covered approximately 57% of the likely sperm whale habitat in the Western Mediterranean and 75% in the Eastern Mediterranean. Approximate total estimates of sperm whale abundance in the Western and Eastern Mediterranean basins based on extrapolation to the unsurveyed areas are 1,678 and 164 whales respectively. This gives an estimate for the whole Mediterranean Sea of 1,842 animals.